3D coverage location modeling of Wi-Fi access point placement in indoor environment. (November 2015) - Lee, Gunhak
Highlights: This paper presents 3D coverage location modeling for indoor Wi-Fi access points. The proposed 3D location model incorporates Wi-Fi signal path loss characteristics. This paper provides a useful framework for 3D facility location modeling. Both coverage and capacity strategies of Wi-Fi deployment are embedded in modeling. This paper shows several practical solutions to indoor Wi-Fi deployment practices. Abstract: Many traditional facility location models have sought optimal solutions in two-dimensional space. However, certain locations in reality need to be modeled in three-dimensional space. This paper addresses a location problem in three-dimensional space from the application perspective. Specifically, we introduce a 3D coverage location model of Wi-Fi access points (APs) in an indoor environment. To do this, we first incorporate a generic radio propagation assuming typical obstructions of a building into the standard coverage model, using 3D Euclidean distance characterizing radio signal penetration. The suggested model is then applied for an efficient AP placement plan in a multi-story building at a university campus. The empirical results present 3D representations of the solutions for multi-floor deployment of Wi-Fi APs. This research is expected to provide a useful modeling framework for combining facility location model with wireless network design in a 3D environment.